Caribbean regional food and nutrition security policy (RFNSP); approved and endorsed by the Council for Economic Trade and Development (COTED) on October 22, 2010 (CARICOM Secretariat GeorgetownGY, 2011)
Seeks to provide a holistic policy framework for the period (2011-2015) that adapts the major elements of regional development agreements and initiatives into concrete policy priorities that will guide the design, implementation and monitoring of programmes which aim to address food and nutiriton security challenges in CARICOM. Focuses on the eradication of extreme hunger and poverty, ensuring environmental sustainability and fostering global partnerships for development.
Available in print and CDRom versions